Nutrition Adequacy Therapeutic Enhancement in the Critically Ill: A Randomized Double‐Blind, Placebo‐Controlled Trial of the Motilin Receptor Agonist Camicinal (GSK962040): The NUTRIATE Study. Issue 5 (28th December 2017) - Deane, Adam M.; Lamontagne, Francois; Dukes, George E.; Neil, David; Vasist, Lakshmi; Barton, Matthew E.; Hacquoil, Kimberley; Ou, Xiaoling; Richards, Duncan; Stelfox, Henry T.; Mehta, Sangeeta; Day, Andrew G.; et al.
Abstract: Background: Camicinal is a novel, nonmacrolide, motilin receptor agonist that accelerates gastric emptying in critically ill patients with established feed intolerance. The primary question was whether the preemptive administration of camicinal increased the provision of enteral nutrition (EN) to critically ill patients with risk factors that predisposed to feed intolerance. Methods: This was an international, multicenter, parallel‐group, blinded, randomized controlled trial. Patients at risk for feed intolerance, defined as receiving moderate to high doses of vasopressors or opiates, or admitted because of multiple traumatic injuries or with brain injury, received either enteral camicinal 50 mg or placebo daily for a maximum of 7 days, along with EN administered according to a standardized feeding protocol. The primary outcome was the daily adequacy of enteral feed delivered, as assessed by percentage of goal volume (delivered/prescribed × 100) before development of intolerance. Results: Eighty‐four patients participated. The administration of camicinal did not result in a statistically significant clinical difference in the daily average percentage goal volume delivered (camicinal vs placebo: 77% [95% confidence interval: 71, 83] vs 68% (58, 78); mean difference 9% [−5, 23]; P = 0.21). Similarly, there were no differences in the percentage goal calories (76% [65, 88] vs 68% [60, 77]) and protein (76% [66, 86] vs 70% [61, 80]) administered, or the incidence of feed intolerance (15% vs 14%). Conclusion: The incidence of feed intolerance was low in both groups. In this cohort the preemptive administration of enteral camicinal did not significantly augment the provision of goal EN.